LOWER AND UPPER BOUNDS FOR MILITARY DEPLOYMENT PLANNING CONSIDERING COMBAT - Singgih, Ivan; Lee, Gyu M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
In the military deployment planning problem (DPP), troops and cargoes are transported from source nodes to destination nodes by using multimodal transportation assets, while considering various constraints, such as the supply availability, demand satisfaction constraints, and availability of required transportation assets. The enemies may exist at several locations to block the transportation of troops and cargoes to the destinations. In order to arrive at the destinations, the troops need to have combats with the enemies, which cause loss of troops. Thus, to satisfy the demands, additional troops may be necessary to be transported. Various transportation modes are used and leads to the introduction of subnodes and subarcs in the graphical representation. A mixed integer programming (MIP) formulation is proposed, which is classified as a fractional programming. A solution method which calculates the lower and upper bounds is developed. Then, the gap between the lower and upper bounds is calculated. The computational results are provided and analyzed